STAGED SURGICAL APPROACH TO THE TREATMENT OF PATIENTS WITH THYROID CYSTS - Timur B. Makhmudov; Ulugbek A. Sherbekov (Central Asian Journal of Medicine, 2025)
We analyzed the surgical treatment of 128 patients with thyroid cysts who underwent surgery due to the presence of cysts measuring 3 centimeters or more in diameter. The surgical treatment of thyroid cysts was analyzed, indications and contraindications for this treatment method were determined, and their effectiveness was assessed. The developed algorithm allows you to choose a treatment method and management tactics for patients with thyroid cysts, depending on the size of the cyst and its morphological picture.